A phosphate positive electrode material and preparation method thereof and lithium ion battery
By reasonably adjusting the carbon coating amount of large and small particles in lithium manganese iron phosphate materials, the material's shortcomings in volume energy density and low-temperature performance are solved, and higher electrochemical performance and rate performance are achieved.
Patent Information
- Application Number
- CN202411404234.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Lithium manganese ferrophosphate material has shortcomings in volume energy density and low temperature performance, and its ionic conductivity and compaction density are low, which limits the improvement of battery performance.
By introducing more carbon coatings into large-particle phosphates, electron conductivity and interface contact are improved; introducing less carbon coatings into small-particle phosphates to reduce specific surface area, and combining the two to improve the compaction density and electrochemical properties of the material.
It realizes more efficient electrochemical reactions of materials under high magnification conditions, improves the voltage stability and rate performance of the battery, while maintaining a lower impedance and specific surface area, and improving the overall electrochemical performance.
Smart Images

Figure CN118899429B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a phosphate positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As a secondary battery, lithium-ion batteries have high energy density and cycle performance, high specific capacity and low carbon and environmental protection, so they can help solve the increasingly severe energy problem. Nowadays, the research on lithium batteries has become a hot topic in many fields. Among them, the positive electrode material plays a core role in the energy capacity and cost-effectiveness of lithium-ion batteries. The safety and electrochemical performance of lithium-ion batteries are largely determined by the positive electrode material, so the design and preparation of high-performance positive electrode materials have been widely concerned and studied. Olive-structured lithium iron phosphate (LFP) has a theoretical capacity of 170mAh / g, high electrochemical potential, good thermal stability, environmental friendliness and non-toxicity, and is a good candidate for lithium-ion battery positive electrode materials. However, compared with ternary materials, lithium iron phosphate materials have problems such as low energy density, low voltage platform, and poor low-temperature performance. Therefore, lithium manganese iron phosphate material (LMFP) came into being. Compared with LFP materials, it has higher volume energy density and low-temperature performance, and at the same time has a higher voltage platform. Compared with ternary materials, it has higher safety, lower cost and better cycle performance.
[0003] However, compared with lithium iron phosphate, lithium manganese iron phosphate has lower ionic conductivity and lower compaction density, which severely limits the improvement of its volume energy density. Although current research can effectively improve the compaction density of lithium manganese iron phosphate materials through strategies such as secondary sintering, seed growth, regulation of precursor properties, optimization of sintering process, and size particle grading, this is usually at the expense of a surge in capacity or specific surface area.
[0004] Therefore, how to balance the improvement of the electrochemical properties, physical and chemical properties and compaction density of the positive electrode materials is a key research direction that urgently needs to be studied. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a phosphate positive electrode material and a preparation method thereof and a lithium ion battery. The present invention introduces a larger amount of carbon coating into large-particle phosphate. The higher content of carbon coating improves the electronic conductivity of large particles, so that electrons can be quickly transmitted, which makes up for the problem of poor rate performance of large particles. At the same time, it enhances the interface contact, helps to reduce the interface resistance, improves the transmission efficiency of lithium ions and electrons at the interface, and enables the material to participate in electrochemical reactions more effectively at high rates. In addition, the thicker carbon coating layer can effectively reduce the charge transfer impedance of large particles, making the electrochemical reaction smoother, especially under high rate conditions, the voltage of the battery remains stable, thus showing better rate performance. At the same time, the present invention introduces a smaller amount of carbon coating into small-particle phosphate, and the thinner carbon coating layer can effectively reduce the specific surface area of small particles, solving the problems of increased SEI film thickness, reduced structural stability, increased battery internal resistance, enhanced polarization, and increased first irreversible capacity caused by excessive specific surface area. Therefore, the two work together to make the phosphate positive electrode material have lower impedance, lower specific surface area and higher electrochemical performance while having higher compaction density.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a phosphate positive electrode material, which is a secondary particle of large-particle phosphate and small-particle phosphate after grading. The large-particle phosphate includes a phosphate core and a carbon coating layer coated on the surface of the phosphate core, and the small-particle phosphate includes a phosphate core and a carbon coating layer coated on the surface of the phosphate core.
[0008] The carbon coating amount in the large particle phosphate is greater than the carbon coating amount in the small particle phosphate; wherein the carbon coating amount in the large particle phosphate is based on the mass of the large particle phosphate, and the carbon coating amount in the small particle phosphate is based on the mass of the small particle phosphate.
[0009] It should be noted that the lithium ion diffusion path of large particles is longer, which means that lithium ions need to traverse a longer path inside the particles to diffuse from the surface of the electrode material to the core area. This longer diffusion path will increase the time for lithium ion migration, slow down the reaction rate of the battery during charging and discharging, and lead to a decrease in rate performance. At the same time, the electrochemical reaction kinetics are limited, larger particles have a smaller specific surface area, and fewer active sites, resulting in a decrease in the reaction rate of the electrode material. This rate limitation is particularly evident during high-rate charging and discharging, resulting in a significant decrease in rate performance. Secondly, larger particles are prone to uneven packing density of electrode materials, thereby increasing the internal resistance of the battery. Increased internal resistance will cause the battery to have an increased ohmic polarization during high-rate discharge, and the voltage will drop rapidly, affecting the output power and rate performance of the battery. More importantly, larger particles may affect the formation of a conductive network, increase the conduction path of electrons in the electrode, and lead to limited electronic conductivity. This will further increase the internal resistance of the electrochemical reaction, especially at high rates, where the speed limitation of electron transmission will significantly affect the performance of the battery. In addition, if the specific surface area of small particles is too large, it will lead to problems such as increased SEI film thickness, reduced structural stability, increased battery internal resistance, enhanced polarization, and increased first irreversible capacity.
[0010] To this end, the present invention introduces more carbon coating in large-particle phosphate on the one hand, and the higher content of carbon coating improves the electronic conductivity of large particles, so that electrons can be quickly transmitted, which makes up for the problem of poor rate performance of large particles. At the same time, the interface contact is enhanced, which helps to reduce the interface resistance, improve the transmission efficiency of lithium ions and electrons at the interface, and enable the material to participate in electrochemical reactions more effectively at high rates. In addition, the thicker carbon coating layer can effectively reduce the charge transfer impedance of large particles, making the electrochemical reaction smoother, especially under high rate conditions, the voltage of the battery remains stable, and thus shows better rate performance. At the same time, the capacity performance of large-particle phosphate is also significantly improved. On the other hand, the present invention introduces less carbon coating in small-particle phosphate, and the thinner carbon coating layer can effectively reduce the influence of the holes of the carbon coating layer on the specific surface area, reduce the specific surface area of small particles, and solve the problems of increased SEI film thickness, reduced structural stability, increased battery internal resistance, enhanced polarization, and increased first irreversible capacity caused by excessive specific surface area. Therefore, the two work together to make the phosphate positive electrode material have lower impedance, lower specific surface area and higher electrochemical performance while having higher compaction density.
[0011] In the present invention, illustratively, the phosphate positive electrode material may be, for example, a lithium iron phosphate positive electrode material and / or a lithium iron manganese phosphate positive electrode material.
[0012] In the present invention, the interstitial effect between large phosphate particles and small phosphate particles can significantly increase the compaction density of the phosphate positive electrode material.
[0013] Preferably, the large-particle phosphate includes large-particle lithium iron manganese phosphate and / or large-particle lithium iron phosphate.
[0014] Preferably, the small particle phosphate includes small particle lithium manganese iron phosphate and / or small particle lithium iron phosphate.
[0015] Preferably, the mass ratio of the large particle phosphate to the small particle phosphate is 1:(1-9), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9, etc.
[0016] In the present invention, the mass ratio of large-particle phosphate to small-particle phosphate is 1:(1-9), and this range helps to improve the capacity and compaction performance of the phosphate positive electrode material, and the specific surface area of the phosphate positive electrode material is appropriate, which is conducive to achieving the capacity and rate performance of the phosphate positive electrode material.
[0017] Preferably, the particle size D50 of the large particle phosphate is 300-500 nm, for example, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm.
[0018] Preferably, the particle size D50 of the small particle phosphate is 50-200 nm, for example, 50 nm, 100 nm, 150 nm or 200 nm.
[0019] Preferably, the carbon coating amount in the large particle phosphate (i.e. based on the large particle phosphate) is 1.8-2.5wt%, for example, it can be 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt% or 2.5wt%.
[0020] In the present invention, the carbon coating amount in the large-particle phosphate is 1.8-2.5wt%, which is beneficial to reduce the overall residual carbon content of the phosphate positive electrode material within this range, obtain a phosphate positive electrode material with a suitable specific surface area and a stable structure, and at the same time, the large-particle phosphate can further grow to a suitable size to increase the compaction density.
[0021] Preferably, the carbon coating amount in the small particle phosphate (i.e. based on the small particle phosphate) is 1.3-1.7wt%, for example, it can be 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt% or 1.7wt%.
[0022] In the present invention, the carbon coating amount in the small particle phosphate is 1.3-1.7wt%, which is beneficial to the capacity of the small particles, reduces the impedance of the phosphate positive electrode material, and improves the electrochemical capacity.
[0023] Preferably, the specific surface area of the phosphate positive electrode material is 15-22 m 2 / g, for example, it can be 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g or 22m 2 / g, etc.
[0024] In the present invention, a suitable specific surface area is beneficial to the homogenization process, and is also beneficial to improving the structural stability of the material, reducing the internal resistance and polarization of the battery, and improving the reversible capacity of the material.
[0025] Preferably, the compaction density of the phosphate cathode material is 2.35-2.5 g / cm 3 , for example, it can be 2.35 g / cm 3 , 2.4g / cm 3 , 2.45g / cm 3 or 2.5g / cm 3 wait.
[0026] In the present invention, suitable compaction density is beneficial to improving the volume energy density of the material.
[0027] In a second aspect, the present invention provides a method for preparing the phosphate positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0028] (1) The large-particle phosphate precursor and the small-particle phosphate precursor are subjected to a first calcination to obtain a large-particle calcined material and a small-particle calcined material respectively.
[0029] (2) The large particle first calcined material and the small particle first calcined material are mixed with a carbon source respectively, and then heat-treated respectively to obtain large particle second calcined material and small particle second calcined material. The large particle second calcined material and the small particle second calcined material are then mixed and subjected to a second calcination to obtain large particle phosphate and small particle phosphate, thereby obtaining the phosphate positive electrode material.
[0030] The carbon coating amount in the large particle phosphate is greater than the carbon coating amount in the small particle phosphate; wherein the carbon coating amount in the large particle phosphate is based on the mass of the large particle phosphate, and the carbon coating amount in the small particle phosphate is based on the mass of the small particle phosphate.
[0031] Preferably, the method for preparing the large particle phosphate precursor and the small particle phosphate precursor in step (1) comprises:
[0032] The metal element source and the phosphate raw material are mixed according to the atomic ratio, sand-milled for different times, and dried to obtain the large-particle phosphate precursor and the small-particle phosphate precursor respectively.
[0033] The invention adjusts the particle size of the particles by adjusting the sand milling time, and obtains phosphate precursors of required sizes for subsequent grading.
[0034] It should be noted that the present invention does not limit the specific type of phosphate raw material. For example, it can be manganese dihydrogen phosphate or iron phosphate.
[0035] Preferably, the metal element source includes a lithium source and an iron source.
[0036] It should be noted that the present invention does not limit the specific type of lithium source, and illustratively, it may be lithium carbonate, etc.; the present invention does not limit the specific type of iron source, and illustratively, it may be iron phosphate, etc.
[0037] Preferably, the metal element source further includes a manganese source and a doping metal source.
[0038] It should be noted that the present invention does not limit the specific type of manganese source. For example, it can be manganese carbonate or manganese dihydrogen phosphate.
[0039] Preferably, the doping metal source includes any one of a magnesium source, a titanium source, a vanadium source, a calcium source, a cobalt source or a zirconium source, or a combination of at least two thereof. Exemplarily, the magnesium source may be magnesium carbonate pentahydrate or the like.
[0040] Preferably, a carbon source is added during the mixing process of the metal element source and the phosphate raw material, and the amount of the carbon source added accounts for 1-4wt% of the total amount of the metal element source and the phosphate raw material, for example, 1wt%, 2wt%, 3wt% or 4wt%, etc. Exemplarily, the carbon source may be glucose and / or polyethylene glycol, etc.
[0041] Preferably, the sand grinding time for obtaining the large-particle phosphate precursor is 5-15 min, for example, 5 min, 10 min or 15 min.
[0042] Preferably, the sand milling time for obtaining the small particle phosphate precursor is 30-70 min, for example, 30 min, 40 min, 50 min, 60 min or 70 min.
[0043] Preferably, in step (1), the temperature of the first calcination to obtain the large particle sintered material is 500-600°C, for example, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, and the time is 4-8h, for example, 4h, 5h, 6h, 7h or 8h.
[0044] In the present invention, the appropriate calcination temperature of the large particle-sintered material is beneficial to improving the compaction density of the phosphate positive electrode material, preventing the large particle size from being too large, and improving the performance of the phosphate positive electrode material, such as the rate performance.
[0045] Preferably, in step (1), the temperature of the first calcination to obtain the small particles of the sintered material is 400-500°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C, and the time is 4-8h, for example, 4h, 5h, 6h, 7h or 8h.
[0046] In the present invention, the appropriate calcination temperature of the small particles is conducive to improving the phase purity and crystallinity of the phosphate positive electrode material, and the small particles are of appropriate size, which can provide high capacity and improve the electrochemical performance of the phosphate positive electrode material.
[0047] Preferably, the carbon source in step (2) comprises any one of glucose, polyethylene glycol, sucrose, polyvinyl pyrrolidone, citric acid or carbon nanotubes, or a combination of at least two thereof.
[0048] Preferably, in the process of mixing the large particle-fuel and the carbon source in step (2), the mass of the carbon source accounts for 10-15% of the mass of the large particle-fuel, for example, it can be 10%, 11%, 12%, 13%, 14% or 15%.
[0049] Preferably, in the process of mixing the small particles-furnace and the carbon source in step (2), the mass of the carbon source accounts for 5-10% of the mass of the small particles-furnace, for example, it can be 5%, 6%, 7%, 8%, 9% or 10%.
[0050] Preferably, during the mixing process in step (2), the mass ratio of the large-particle sintered material to the small-particle sintered material is 1:(1-9), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9.
[0051] Preferably, the method of mixing the large-particle sintered material and the small-particle sintered material in step (2) includes crushing or ball milling.
[0052] In the present invention, the phosphate positive electrode material in a secondary particle structure can be broken up by pulverizing or ball milling, and the breaking up of the secondary particle structure promotes the filling and mixing uniformity of the large particle sintered material and the small particle sintered material.
[0053] Preferably, the temperature of the second calcination in step (2) is 680-800°C, for example, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, and the time is 4-8h, for example, 4h, 5h, 6h, 7h or 8h.
[0054] In the present invention, if the temperature of the second calcination is too low, the particles cannot grow to a suitable size, the material compaction is low, and the impedance is large; if the temperature of the second calcination is too high, impurities may be generated, seriously affecting the electrochemical capacity and rate performance of the material.
[0055] Preferably, the preparation method comprises the following steps:
[0056] (1) A lithium source, an iron source, a manganese source, a doped metal source, a carbon source and a phosphate raw material are mixed according to an atomic ratio, and after basket milling for 40-80 min (for example, 40 min, 50 min, 60 min, 70 min or 80 min, etc.), sand milling for 5-15 min and 30-70 min, respectively, a large particle slurry and a small particle slurry are obtained, and then the large particle slurry and the small particle slurry are dried to obtain a large particle phosphate precursor and a small particle phosphate precursor, respectively.
[0057] (2) In an inert atmosphere (illustratively, nitrogen, etc.), the large particle phosphate precursor and the small particle phosphate precursor are subjected to a first calcination to obtain a large particle sintered material and a small particle sintered material respectively.
[0058] The first calcination temperature for obtaining the large particles is 500-600°C, and the time is 4-8 hours; the first calcination temperature for obtaining the small particles is 400-500°C, and the time is 4-8 hours.
[0059] (3) The large particle first calcined material and the small particle first calcined material are mixed with a carbon source respectively, and then basket milled and spray dried respectively to obtain large particle second calcined material and small particle second calcined material. The large particle second calcined material and the small particle second calcined material are then mixed in a mass ratio of 1:(1-9), and then a second calcination is performed in an inert atmosphere (exemplarily, such as nitrogen, etc.). The temperature of the second calcination is 680-800°C and the time is 4-8h. After crushing, large particle phosphate and small particle phosphate are obtained to obtain the phosphate positive electrode material.
[0060] Among them, in the process of mixing large particles and carbon source, the mass of carbon source accounts for 10-15% of the mass of large particles; in the process of mixing small particles and carbon source, the mass of carbon source accounts for 5-10% of the mass of small particles.
[0061] In a third aspect, the present invention provides a lithium-ion battery, wherein the positive electrode plate of the lithium-ion battery comprises the phosphate positive electrode material as described in the first aspect.
[0062] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0063] Compared with the prior art, the present invention has the following beneficial effects:
[0064] The present invention introduces a larger amount of carbon coating into large-particle phosphate, and the higher content of carbon coating improves the electronic conductivity of large particles, so that electrons can be quickly transmitted, which makes up for the problem of poor rate performance of large particles. At the same time, the interface contact is enhanced, which helps to reduce the interface resistance, improve the transmission efficiency of lithium ions and electrons at the interface, and enable the material to participate in electrochemical reactions more effectively at high rates. In addition, the thicker carbon coating layer can effectively reduce the charge transfer impedance of large particles, making the electrochemical reaction smoother, especially under high rate conditions, the voltage of the battery remains stable, thus showing better rate performance. At the same time, the present invention introduces a smaller amount of carbon coating into small-particle phosphate, and the thinner carbon coating layer can effectively reduce the specific surface area of small particles, solving the problems of increased SEI film thickness, reduced structural stability, increased battery internal resistance, enhanced polarization, and increased first irreversible capacity caused by excessive specific surface area. Therefore, the two cooperate with each other, so that the phosphate positive electrode material has lower impedance, lower specific surface area, and higher electrochemical performance while having a higher compaction density. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is a SEM image of the lithium manganese iron phosphate positive electrode material provided in Example 1 of the present invention.
[0066] Figure 2 This is a SEM image of large particles of the lithium iron manganese phosphate positive electrode material provided in Example 1 of the present invention after classification treatment.
[0067] Figure 3 This is a SEM image of small particles of the lithium iron manganese phosphate positive electrode material provided in Example 1 of the present invention after classification treatment. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0069] Example 1
[0070] The present embodiment provides a lithium iron manganese phosphate positive electrode material, which includes large-particle lithium iron manganese phosphate and small-particle lithium iron manganese phosphate. The large-particle lithium iron manganese phosphate includes a lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate core, and the small-particle lithium iron manganese phosphate includes a lithium iron manganese phosphate core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate core.
[0071] Based on the mass of large-particle lithium manganese iron phosphate, the carbon coating amount in the large-particle lithium manganese iron phosphate is 2.3wt%, and based on the mass of small-particle lithium manganese iron phosphate, the carbon coating amount in the small-particle lithium manganese iron phosphate is 1.5wt%.
[0072] The mass ratio of the large-particle lithium iron manganese phosphate to the small-particle lithium iron manganese phosphate is 1:2.33.
[0073] The particle size D50 of the large-particle lithium manganese iron phosphate is 430 nm, and the particle size D50 of the small-particle lithium manganese iron phosphate is 120 nm.
[0074] The specific surface area of the lithium manganese iron phosphate positive electrode material is 16.5 m 2 / g, compacted density is 2.46g / cm 3 .
[0075] This embodiment also provides a method for preparing the above-mentioned lithium iron manganese phosphate positive electrode material, and the preparation method comprises the following steps:
[0076] (1) 371.07 g of manganese carbonate, 970.12 g of manganese dihydrogen phosphate, and 600.92 g of ferric phosphate were added to 4000 g of cold water and stirred. Then, 377.97 g of lithium carbonate was added and stirred until there were no bubbles. Then, 8000 g of cold water was added and stirred evenly. Subsequently, 30 g of magnesium phosphate pentahydrate, 15.72 g of glucose, and 15.72 g of polyethylene glycol were added. After the mixture was stirred, 3000 g of cold water was added to obtain a source slurry.
[0077] The source slurry was placed in a basket mill for coarse grinding for 60 minutes, and then transferred to a sand mill for sand grinding for 10 minutes to obtain a slurry with large particles, and then sand ground for 60 minutes to obtain a slurry with small particles.
[0078] The large particle slurry and the small particle slurry are spray-dried respectively to obtain a large particle phosphate precursor and a small particle phosphate precursor.
[0079] (2) In a nitrogen atmosphere, the large-particle phosphate precursor was first calcined at a heating rate of 3°C / min to 550°C for 6 hours to obtain a large-particle first-sintered material; the small-particle phosphate precursor was first calcined at a heating rate of 3°C / min to 450°C for 6 hours to obtain a small-particle first-sintered material.
[0080] (3) Disperse 200 g of the large particle one calcined material, 20 g of glucose and 4 g of polyethylene glycol in 1 L of water, wherein the total mass of glucose and polyethylene glycol accounts for 12% of the mass of the large particle one calcined material; stir evenly, grind with a basket mill for 60 min, and then spray dry to obtain a large particle two calcined material; disperse 200 g of the small particle one calcined material, 12 g of glucose and 4 g of polyethylene glycol in 1 L of water, wherein the total mass of glucose and polyethylene glycol accounts for 8% of the mass of the small particle one calcined material; stir evenly, grind with a basket mill for 60 min, and then sand grind with a sand mill for 60 min, and then spray dry to obtain a large particle two calcined material.
[0081] 30 g of large-particle sintered material and 70 g of small-particle sintered material were mixed in a high-speed crusher for 10 min, and then the temperature was raised to 750°C at a rate of 3°C / min in a nitrogen atmosphere for a second calcination. The second calcination time was 6 h. After crushing, large-particle lithium iron manganese phosphate and small-particle lithium iron manganese phosphate were obtained to obtain the lithium iron manganese phosphate positive electrode material.
[0082] Figure 1 The SEM image of the lithium manganese iron phosphate positive electrode material prepared in this embodiment is shown. It can be seen from the figure that the particle size of the large particles is about 430nm, and the particle size of the small particles is about 120nm. The grading and gap filling of the two can effectively improve the compaction density of the material.
[0083] The lithium iron manganese phosphate positive electrode material provided in this embodiment is subjected to classification treatment, and the specific steps include: placing the lithium iron manganese phosphate positive electrode material in a high-speed pulverizer for 20 minutes to crush the secondary ball particles, and then performing air flow classification on the crushed particles, and separating the large and small particles under the action of the classification vortex force of the air flow classifier. The separated large and small particles are subjected to SEM testing, and the obtained SEM images are as follows: Figure 2 and Figure 3 shown.
[0084] Example 2
[0085] The difference between this embodiment and embodiment 1 is that the masses of the large-particle sintered material and the small-particle sintered material in the adjustment step (3) are 10 g and 90 g, respectively.
[0086] The rest of the preparation methods and parameters were the same as those in Example 1.
[0087] Example 3
[0088] The difference between this embodiment and embodiment 1 is that the masses of the large-particle sintered material and the small-particle sintered material in the adjustment step (3) are 20 g and 80 g respectively.
[0089] The rest of the preparation methods and parameters were the same as those in Example 1.
[0090] Example 4
[0091] The difference between this embodiment and embodiment 1 is that the masses of the large-particle sintered material and the small-particle sintered material in the adjustment step (3) are 50 g and 50 g respectively.
[0092] The rest of the preparation methods and parameters were the same as those in Example 1.
[0093] Example 5
[0094] The difference between this embodiment and embodiment 1 is that the high-speed crusher in step (3) is replaced by a ball mill.
[0095] The rest of the preparation methods and parameters were the same as those in Example 1.
[0096] Example 6
[0097] The difference between this embodiment and embodiment 1 is that the masses of the large-particle sintered material and the small-particle sintered material in the adjustment step (3) are 66.7 g and 33.3 g.
[0098] The rest of the preparation methods and parameters were the same as those in Example 1.
[0099] Example 7
[0100] The difference between this embodiment and embodiment 1 is that the masses of the large-particle sintered material and the small-particle sintered material in the adjustment step (3) are 7.7 g and 92.3 g.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Example 8
[0103] The difference between this embodiment and embodiment 1 is that the masses of glucose and polyethylene glycol mixed with the large particle burnt material in step (3) are adjusted to 32 g and 4 g.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Example 9
[0106] The difference between this embodiment and embodiment 1 is that the masses of glucose and polyethylene glycol mixed with the small particle-burnt material in step (3) are adjusted to 10 g and 2 g.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 10
[0109] The difference between this embodiment and embodiment 1 is that the temperature for the first calcination of the large-particle lithium manganese iron phosphate precursor in step (2) is 400°C.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Embodiment 11
[0112] The difference between this embodiment and embodiment 1 is that the temperature for the first calcination of the large-particle lithium manganese iron phosphate precursor in step (2) is 700°C.
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] Example 12
[0115] The difference between this embodiment and embodiment 1 is that the temperature for the first calcination of the small particle lithium manganese iron phosphate precursor in step (2) is 300°C.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Example 13
[0118] The difference between this embodiment and embodiment 1 is that the temperature for the first calcination of the small particle lithium manganese iron phosphate precursor in step (2) is 600°C.
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Embodiment 14
[0121] The difference between this embodiment and embodiment 1 is that the temperature of the second calcination in step (3) is 650°C.
[0122] The rest of the preparation methods and parameters were the same as those in Example 1.
[0123] Embodiment 15
[0124] The difference between this embodiment and embodiment 1 is that the temperature of the second calcination in step (3) is 850°C.
[0125] The rest of the preparation methods and parameters were the same as those in Example 1.
[0126] Example 16
[0127] The present embodiment provides a lithium iron phosphate positive electrode material, including large-particle lithium iron phosphate and small-particle lithium iron phosphate. The large-particle lithium iron phosphate includes a lithium iron phosphate core and a carbon coating layer coated on the surface of the lithium iron phosphate core. The small-particle lithium iron phosphate includes a lithium iron phosphate core and a carbon coating layer coated on the surface of the lithium iron phosphate core.
[0128] Based on the mass of the large-particle lithium iron phosphate, the carbon coating amount in the large-particle lithium iron phosphate is 1.8wt%, and based on the mass of the small-particle lithium iron phosphate, the carbon coating amount in the small-particle lithium iron phosphate is 1.3wt%.
[0129] The particle size D50 of the large-particle lithium iron phosphate is 470 nm, and the particle size D50 of the small-particle lithium iron phosphate is 140 nm.
[0130] The specific surface area of the lithium iron phosphate positive electrode material is 13.5 m 2 / g, compacted density is 2.66g / cm 3 .
[0131] This embodiment also provides a method for preparing the above-mentioned lithium iron phosphate positive electrode material, and the preparation method comprises the following steps:
[0132] (1) 1669.22 g of ferric phosphate was added to 4000 g of cold water and stirred, and then 377.97 g of lithium carbonate was added and stirred until there were no bubbles, and then 8000 g of cold water was added and stirred evenly, followed by the addition of 30 g of magnesium phosphate pentahydrate, 15.72 g of glucose and 15.72 g of polyethylene glycol, and after the mixture was stirred, 3000 g of cold water was added to obtain a source slurry.
[0133] The source slurry was placed in a basket mill for coarse grinding for 60 min, and then transferred to a sand mill for sand grinding for 10 min to obtain a slurry with large particles, and then sand ground for 60 min to obtain a slurry with small particles.
[0134] The large particle slurry and the small particle slurry are spray-dried respectively to obtain a large particle phosphate precursor and a small particle phosphate precursor.
[0135] (2) In a nitrogen atmosphere, the large-particle phosphate precursor was first calcined at a heating rate of 3°C / min to 550°C for 6 hours to obtain a large-particle first-sintered material; the small-particle phosphate precursor was first calcined at a heating rate of 3°C / min to 450°C for 6 hours to obtain a small-particle first-sintered material.
[0136] (3) Disperse 200 g of the large particle one calcined material, 14 g of glucose and 4 g of polyethylene glycol in 1 L of water, wherein the total mass of glucose and polyethylene glycol accounts for 12% of the mass of the large particle one calcined material; stir evenly, grind with a basket mill for 60 min, and then spray dry to obtain a large particle two calcined material; disperse 200 g of the small particle one calcined material, 8 g of glucose and 4 g of polyethylene glycol in 1 L of water, wherein the total mass of glucose and polyethylene glycol accounts for 8% of the mass of the small particle one calcined material; stir evenly, grind with a basket mill for 60 min, and then sand grind with a sand mill for 60 min, and then spray dry to obtain a large particle two calcined material.
[0137] 30 g of large-particle sintered material and 70 g of small-particle sintered material were mixed in a high-speed crusher at a mass ratio of 1:2.33 for 10 minutes, and then the temperature was raised to 750°C at a rate of 3°C / min in a nitrogen atmosphere for a second calcination. The second calcination time was 6 hours. After crushing, large-particle lithium iron phosphate and small-particle lithium iron phosphate were obtained to obtain the lithium iron phosphate positive electrode material.
[0138] Comparative Example 1
[0139] The difference between this comparative example and Example 1 is that the carbon coating amount in the large-particle lithium manganese iron phosphate is equal to the carbon coating amount in the small-particle lithium manganese iron phosphate, that is, the masses of glucose and polyethylene glycol mixed with the large-particle calcined material in the adjustment step (3) are 12g and 4g respectively.
[0140] The rest of the preparation methods and parameters were the same as those in Example 1.
[0141] Comparative Example 2
[0142] The difference between this comparative example and Example 1 is that the carbon coating amount in the large-particle lithium manganese iron phosphate is equal to the carbon coating amount in the small-particle lithium manganese iron phosphate, that is, the masses of glucose and polyethylene glycol mixed with the small-particle calcined material in the adjustment step (3) are 20 g and 4 g, respectively.
[0143] The rest of the preparation methods and parameters were the same as those in Example 1.
[0144] Comparative Example 3
[0145] The difference between this comparative example and Example 1 is that the carbon coating amount in the large-particle lithium manganese iron phosphate is less than the carbon coating amount in the small-particle lithium manganese iron phosphate, that is, the masses of glucose and polyethylene glycol mixed with the large-particle one-burnt material in the adjustment step (3) are 12 g and 4 g, respectively, and the masses of glucose and polyethylene glycol mixed with the small-particle one-burnt material are 20 g and 4 g, respectively.
[0146] The rest of the preparation methods and parameters were the same as those in Example 1.
[0147] Performance Testing
[0148] 1. The specific surface area, compaction density, impedance and carbon content of the lithium manganese iron phosphate positive electrode materials prepared in the above examples and comparative examples were tested.
[0149] 1) Specific surface area test: The specific surface area and pore size distribution curve of the material are determined by the nitrogen low-temperature adsorption method. Generally, the sample is first heated and vacuumed to remove the impurity gas adsorbed on the surface. Then it is weighed and placed in liquid nitrogen. At liquid nitrogen temperature, the nitrogen adsorption of the sample is measured at different pre-set pressure points to obtain the adsorption isotherm; then the data is processed by computer to calculate the specific surface area from the adsorption isotherm.
[0150] 2) Compaction density test: Use a compaction density meter to test the compaction density. Under the condition of 25℃±2℃, load the cleaned empty mold (including the upper and lower test electrodes / gaskets) into the test equipment, and use the matching test software to reset the thickness. After the reset is completed, weigh an appropriate amount of the sample to be tested and load it into the mold. Vibrate the sample appropriately, install the test electrodes / gaskets, load the mold into the test equipment, and start the part test.
[0151] 3) Impedance: The Princeton electrochemical workstation was used to test the alternating current impedance spectroscopy (EIS) of the material. The test conditions were: the amplitude of the AC excitation signal was 10mV and the frequency range was 10 -2 -10 5 Hz, and the voltage range is between 2.0-4.3V.
[0152] 4) Carbon content test: The phosphate positive electrode material is graded, and then the carbon coating amount of the separated large and small particles is tested respectively. The test steps of the carbon coating amount include: placing the carbon-sulfur analyzer on a stable, vibration-free workbench without direct sunlight and adjusting it to a horizontal level, placing the sample in a dry porcelain crucible and then placing it in the carbon-sulfur analyzer for testing.
[0153] 5) Particle size D50 test: SEM is used to count the particle sizes of one hundred spherical nanoparticles to obtain D50.
[0154] 6) Mass ratio test of large-particle phosphate and small-particle phosphate: The phosphate positive electrode material is placed in a high-speed pulverizer for 20 minutes to break the secondary ball particles, and then the broken particles are subjected to air flow classification. The large and small particles are separated under the action of the classification vortex force of the air flow classifier, and then they are weighed separately to calculate the mass ratio.
[0155] 2. The electrochemical performance of the phosphate cathode materials prepared in the above embodiments and comparative examples was tested, including specific capacity, rate performance and volume energy density tests.
[0156] 1) Specific capacity test: At 25°C and normal pressure (0.1MPa), the positive electrode material, conductive carbon black, and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in N-methylpyrrolidone solvent at a mass percentage ratio of 90:5:5 to obtain a positive electrode slurry, and then the positive electrode slurry was coated on an aluminum foil, and after drying and cold pressing, a positive electrode sheet containing a 100μm thick positive electrode active layer was obtained; then the positive electrode sheet was punched into a small disc with a diameter of 12mm with a film mold, and after drying and weighing, a button battery was assembled in a glove box under Ar protective atmosphere using a 2025 button battery shell, a Li metal disc as the negative electrode, and a conventional high-voltage lithium cobalt oxide electrolyte. After assembly, the battery was charged at a constant current of 0.1C / 1C / 4C to 4.3V, and then charged at a constant voltage of 4.3V to a current of 0.05C. The charging capacity at this time was recorded as the first-cycle charging capacity. After that, the battery was allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C / 1C / 4C to a voltage of 2.0V. The discharge capacity was recorded as the first-cycle discharge capacity of the battery.
[0157] 2) Rate performance test: According to the method in the buckle capacity test, the positive electrode material is coated into a positive electrode sheet, and the negative electrode is graphite, which is used together with the polyethylene diaphragm and the electrolyte (the electrolyte is LiPF6, and the solvent is EC / DMC) to form a full battery. Then charge at a constant current of 0.1C to a voltage of 4.3V, and charge at a constant voltage at a voltage of 4.3V to a current equal to 0.05C, then let it stand for 5 minutes, and then discharge at a constant current of 0.1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 0.1C; let it stand for 10 minutes, charge at a constant current of 1C to a voltage of 4.3V, and then charge at a constant voltage of 4.3V to a current equal to 0.05C, then let it stand for 5 minutes, and then discharge at a constant current of 1C to a voltage of 2.5V. At this time, The capacity is recorded as the discharge capacity at 1C rate; after standing for 10 minutes, charge at a constant current of 4C rate to a voltage of 4.3V, then charge at a constant voltage at 4.3V to a current equal to 0.05C, then stand for 5 minutes, and discharge at a constant current of 4C rate to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at 4C rate. The discharge capacity at 1C rate divided by the discharge capacity at 0.1C rate is the 1C rate performance; the discharge capacity at 4C rate divided by the discharge capacity at 1C rate is the 4C rate performance.
[0158] Volume energy density: Volume energy density = gram capacity × compaction density × average voltage.
[0159] The test results are shown in Table 1.
[0160] Table 1
[0161]
[0162]
[0163]
[0164] analyze:
[0165] It can be seen from the above table that the present invention introduces a larger carbon coating amount into the large-particle lithium manganese iron phosphate and a smaller carbon coating amount into the small-particle phosphate. The two cooperate with each other, so that the phosphate positive electrode material has a lower impedance, a lower specific surface area and a higher electrochemical performance while having a higher compaction density.
[0166] It can be seen from Example 1 and Examples 6-7 that if the mass ratio of large-particle lithium manganese iron phosphate to small-particle lithium manganese iron phosphate is too large, the capacity and rate performance will decrease. If the mass ratio of large-particle lithium manganese iron phosphate to small-particle lithium manganese iron phosphate is too small, the BET (specific surface area) will be too high and the compaction density will be reduced.
[0167] It can be seen from Example 1 and Examples 8-9 that if the carbon coating amount in the large-particle lithium manganese iron phosphate is too large, the BET will be too high and the compaction density will be reduced; if the carbon coating amount in the small-particle lithium manganese iron phosphate is too small, the capacity and rate performance will decrease, the compaction density will increase to a certain extent, but the volume energy density will decrease.
[0168] It can be seen from Example 1 and Examples 10-11 that if the temperature of the first calcination of the large-particle lithium manganese iron phosphate precursor is too low, the compaction density will be reduced and the BET will be slightly higher; if the temperature of the first calcination of the large-particle lithium manganese iron phosphate precursor is too high, the capacity and rate performance will be seriously reduced.
[0169] It can be seen from Examples 1 and 12-13 that if the temperature of the first calcination of the small-particle lithium manganese iron phosphate precursor is too low, the capacity will decrease; if the temperature of the first calcination of the small-particle lithium manganese iron phosphate precursor is too high, the capacity will decrease.
[0170] It can be seen from Example 1 and Examples 14-15 that if the temperature of the second calcination is too low, the compaction density will be seriously reduced; if the temperature of the second calcination is too high, the capacity and rate performance will be seriously reduced.
[0171] It can be seen from Example 1 and Comparative Example 1 or 2 that if the carbon coating amount in the large-particle lithium manganese iron phosphate is equal to the carbon coating amount in the small-particle lithium manganese iron phosphate, the capacity and rate performance will decrease, and the volume energy density will be lower.
[0172] It can be seen from Example 1 and Comparative Example 3 that if the carbon coating amount in the large-particle lithium manganese iron phosphate is less than the carbon coating amount in the small-particle lithium manganese iron phosphate, it will lead to too high BET, reduced compaction density and low volume energy density.
[0173] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: (1) Mixing the metal element source and the phosphate raw material according to the atomic ratio, sand grinding for 5-15 minutes, and drying to obtain a large-particle phosphate precursor, and sand grinding for 30-70 minutes and drying to obtain a small-particle phosphate precursor; The large-particle phosphate precursor is first calcined at 500-560° C. to obtain a large-particle first sinter, and the small-particle phosphate precursor is first calcined at 400-460° C. to obtain a small-particle first sinter; (2) mixing the large particle first calcined material and the small particle first calcined material with the same carbon source material respectively, and then heat treating them respectively to obtain large particle second calcined material and small particle second calcined material, and then mixing the large particle second calcined material and the small particle second calcined material, and performing a second calcination to obtain large particle phosphate and small particle phosphate, thereby obtaining the phosphate positive electrode material; The phosphate positive electrode material is lithium iron manganese phosphate or lithium iron phosphate; The phosphate positive electrode material is composed of large-particle phosphate and small-particle phosphate, wherein the large-particle phosphate includes a phosphate core and a carbon coating layer coated on the surface of the phosphate core, and the small-particle phosphate includes a phosphate core and a carbon coating layer coated on the surface of the phosphate core; The carbon coating amount in the large particle phosphate is greater than the carbon coating amount in the small particle phosphate; wherein the carbon coating amount in the large particle phosphate is based on the mass of the large particle phosphate, and the carbon coating amount in the small particle phosphate is based on the mass of the small particle phosphate; The mass ratio of the large particle phosphate to the small particle phosphate is 1:(2-9); The particle size D50 of the large particle phosphate is 300-500nm; The particle size D50 of the small particle phosphate is 50-200 nm; The carbon coating amount in the large particle phosphate is 1.8-2.5wt%; The carbon coating amount in the small particle phosphate is 1.3-1.7wt%.
2. The preparation method according to claim 1, characterized in that: The specific surface area of the phosphate positive electrode material is 15-22 m 2 / g; And / or, the compaction density of the phosphate positive electrode material is 2.35-2.5 g / cm 3 .
3. The preparation method according to claim 1, characterized in that: The metal element source includes a lithium source and an iron source; And / or, the metal element source further includes a manganese source and a doping metal source; the doping metal source includes any one of a magnesium source, a titanium source, a vanadium source, a calcium source, a cobalt source or a zirconium source, or a combination of at least two thereof; And / or, a carbon source is added to the metal element source and the phosphate raw material during the mixing process, and the amount of the carbon source added accounts for 1-4wt% of the total amount of the metal element source and the phosphate raw material.
4. The preparation method according to claim 1, characterized in that: In step (1), the first roasting time of the large particle sintered material is 4-8 hours; And / or, in step (1), the first roasting time for obtaining the small particles of the sintered material is 4-8 hours.
5. The preparation method according to claim 1, characterized in that: The carbon source in step (2) comprises any one of glucose, polyethylene glycol, sucrose, polyvinyl pyrrolidone, citric acid or carbon nanotubes, or a combination of at least two thereof; and / or, in the process of mixing the large particle-burnt material and the carbon source in step (2), the mass of the carbon source accounts for 10-15% of the mass of the large particle-burnt material; and / or, in the process of mixing the small particles-burnt material and the carbon source in step (2), the mass of the carbon source accounts for 5-10% of the mass of the small particles-burnt material; And / or, during the mixing process of step (2), the mass ratio of the large-particle sintered material to the small-particle sintered material is 1:(2-9); And / or, in step (2), the second calcination temperature is 680-800° C. and the time is 4-8 hours.
6. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing a lithium source, an iron source, a manganese source, a doping metal source, a carbon source and a phosphate raw material according to an atomic ratio, and performing basket milling for 40-80 minutes, and sand milling for 5-15 minutes and 30-70 minutes, respectively, to obtain a large particle slurry and a small particle slurry, and then drying the large particle slurry and the small particle slurry to obtain a large particle phosphate precursor and a small particle phosphate precursor, respectively; (2) In an inert atmosphere, the large particle phosphate precursor and the small particle phosphate precursor are subjected to a first calcination to obtain a large particle one-sintered material and a small particle one-sintered material respectively; The first calcination temperature for obtaining the large particles is 500-560°C and the time is 4-8h; the first calcination temperature for obtaining the small particles is 400-460°C and the time is 4-8h; (3) The large particle first calcined material and the small particle first calcined material are mixed with the same carbon source material respectively, and then basket milled and spray dried respectively to obtain large particle second calcined material and small particle second calcined material, and then the large particle second calcined material and the small particle second calcined material are mixed in a mass ratio of 1:(2-9), and then a second calcination is performed in an inert atmosphere, wherein the temperature of the second calcination is 680-800°C and the time is 4-8h, and after crushing, large particle phosphate and small particle phosphate are obtained to obtain the phosphate positive electrode material; Among them, in the process of mixing large particles and carbon source, the mass of carbon source accounts for 10-15% of the mass of large particles; in the process of mixing small particles and carbon source, the mass of carbon source accounts for 5-10% of the mass of small particles.
7. A lithium ion battery, characterized in that: The positive electrode sheet of the lithium-ion battery includes a phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-compaction low-temperature lithium iron phosphate material, lithium battery positive plate and preparation method thereof
CN113086959A
Phosphate positive electrode material and preparation method and application thereof
CN117303340A
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN118373397A